Implementasi Sistem Informasi Dokumen Pencacah Unit Distribusi Badan Pusat Statistik Sulawesi Selatan - Margono Margono; Rahman Rahman (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2021)
Deputy for distribution statistics and services for the Central Statistics Agency of South Sulawesi (BPS Sulawesi Selatan), who is responsible for scheduling and organizing the Distribution Pattern Survey has difficulties in organizing enumeration documents, both in organizing District BPS documents, and in managing the history of the result surveys that have been conducted. The existing survey management software was not specifically intended for managing enumerator document files. In fact, the results of the evaluation of the enumerator documents determine the further policy regarding the implementation or postponement of the police survey in the South Sulawesi district. This study developed a document enumerator document information system software to facilitate South Sulawesi BPS (BPS Sulsel) in managing enumerator documents. The existence of an enumerator document information system is a practical solution that facilitates data organization while speeding up the document evaluation process. The software is developed using the waterfall development model. Testing software implementation uses the Mean Opinion Score or MOS to assess the success of the software. The test results obtained a 97.5% percentage of the MOS score showing the success of using the software in supporting the process of evaluating the enumerator documents.